RECURRENT STOMAL VARICEAL BLEEDING IN CIRRHOSIS: MANAGEMENT WITH TRANSJUGULAR INTRAHEPATIC PORTOSYSTEMIC SHUNT AND EMBOLIZATION - Armani Scaffaro, Leandro; Farenzena, Mauricio; Alvares-da-Silva, Mario Reis (Clinical and Biomedical Research, 2023)
Gastrointestinal (GI) bleeding is a common complication of cirrhosis and portal hypertension. Most cases are secondary to gastro-esophageal variceal rupture, managed endoscopically. Stomal bleeding is rare and there’s no standard therapy. We present a case of a cirrhotic patient with recurrent stomal hemorrhage successfully treated with transjugular intrahepatic portosystemic shunt (TIPS) and stomal varices embolization. [Absctract truncated]